Zoonotic surveillance for rickettsiae in domestic animals in Kenya - Mutai, B.K.; Wainaina, J.M.; Magiri, C.G.; Ng'ang'a, J.K.; Ithondeka, P.M.; Njagi, O.N.; Jiang, J.; Richards, A.L.; Waitumbi, J.N. (Mary Ann Liebert Inc, 2013)
Abstract Rickettsiae are obligate intracellular bacteria that cause zoonotic and human diseases. Arthropod vectors, such as fleas, mites, ticks, and lice, transmit rickettsiae to vertebrates during blood meals. In humans, the disease can be life threatening. This study was conducted amidst rising reports of rickettsioses among travelers to Kenya. Ticks and whole blood were collected from domestic animals presented for slaughter at major slaughterhouses in Nairobi and Mombasa that receive animals from nearly all counties in the country. Blood samples and ticks were collected from 1019 cattle, 379 goats, and 299 sheep and were screened for rickettsiae by a quantitative PCR (qPCR) assay (Rick17b) using primers and probe that target the genus-specific 17-kD gene (htrA). The ticks were identified using standard taxonomic keys. All Rick17b-positive tick DNA samples were amplified and sequenced with primers sets that target rickettsial outer membrane protein genes (ompA and ompB) and the citrate-synthase encoding gene (gltA). Using the Rick17b qPCR, rickettsial infections in domestic animals were found in 25/32 counties sampled (78.1% prevalence). Infection rates were comparable in cattle (16.3%) and sheep (15.1%) but were lower in goats (7.1%). Of the 596 ticks collected, 139 had rickettsiae (23.3%), and the detection rates were highest in Amblyomma (62.3%; n=104), then Rhipicephalus (45.5%; n=120), Hyalomma (35.9%; n=28), and Boophilus (34.9%; n=30). Following sequencing, 104 out of the 139 Rick17b-positive tick DNA had good reverse and forward sequences for the 3 target genes. On querying GenBank with the generated consensus sequences, homologies of 92-100% for the following spotted fever group (SFG) rickettsiae were identified: Rickettsia africae (93.%, n=97), Rickettsia aeschlimannii (1.9%, n=2), Rickettsia mongolotimonae (0.96%, n=1), Rickettsia conorii subsp. israelensis (0.96%, n=1), Candidatus Rickettsia kulagini (0.96% n=1), and Rickettsia spp. (1.9% n=2). In conclusion, molecular methods were used in this study to detect and identify rickettsial infections in domestic animals and ticks throughout Kenya.